A polyetheretherketone based composite material and preparation method thereof
By adding carboxy polytetrafluoroethylene and modified graphite to the polyether ether ketone powder, and surface modification of the graphite is used to modify the graphite with a silane coupling agent, and preparing the composite material in combination with the blend-melt method, the problem of insufficient tribological properties of the polyether ether ketone composite under dry friction or external lubrication conditions was solved, and significant improvement of wear resistance and self-lubricity was achieved.
Patent Information
- Application Number
- CN202411577675.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing polyether ether ketone-based composite materials have insufficient tribological properties under dry friction or external lubrication conditions, and their wear resistance needs to be improved.
The composite material was prepared by adding carboxy polytetrafluoroethylene and modified graphite to the polyether etherketone powder, and surface modification of the graphite was performed using a silane coupling agent, and the composite material was prepared in combination with the blend-melt method.
The wear resistance and self-lubricity of the composite material are significantly improved, and the average friction coefficient and volume wear rate are optimized from 0.44 and 0.0020mm3s-1 to 0.16 and 0.0007mm3s-1, respectively.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a polyetheretherketone-based composite material and a preparation method thereof. Background Art
[0002] Polyetheretherketone (PEEK) and its composite materials are increasingly used in sliding parts such as gears, bearings and seals in automobiles and aerospace engineering due to their excellent properties such as self-lubrication and high mechanical strength, especially in harsh environments. The superior tribological properties of its composite materials have always been a hot topic of research.
[0003] At present, a lot of research has been done on the tribological behavior of PEEK and its composites under dry friction or external lubrication conditions. Although great achievements have been made in the tribological properties of PEEK under liquid lubrication, there is still potential and urgent need to improve its wear resistance.
[0004] Polytetrafluoroethylene (PTFE) is widely used in the field of tribology due to its self-lubricating properties, good physical and chemical stability, and mature synthesis technology. The self-lubricating properties of PTFE are generally attributed to its low shear strength, low adhesion, and low surface energy. The PTFE structural unit consists of closely arranged polymer chips. During the friction shear process, these fibrils tend to adhere to the sliding surface, which is usually metal, limiting the friction contact between highly oriented PTFE. This self-lubricating mechanism of PTFE is called the formation of transfer film.
[0005] Due to its layered structure, graphite can easily slide along the layer direction during movement, resulting in relatively low hardness. This low hardness property makes graphite widely used in the manufacture of lubricants, pencil leads and high-temperature lubricating materials, but when compounded with a resin matrix, its dispersion in the resin matrix is poor. Summary of the invention
[0006] In order to improve the wear resistance of a polyetheretherketone-based composite material, the present invention provides a wear-resistant polyetheretherketone-based composite material and a preparation method thereof.
[0007] The technical solution of the present invention is as follows:
[0008] A polyetheretherketone-based composite material comprises the following components in parts by weight:
[0009] 50 to 90 parts of hydroxylated polyetheretherketone powder, 10 to 40 parts of carboxyl-containing polytetrafluoroethylene, 10 to 40 parts of modified graphite, 1 to 10 parts of silane coupling agent, and 3 to 10 parts of auxiliary filler;
[0010] The hydroxylated polyetheretherketone powder is obtained by uniformly mixing dry polyetheretherketone powder and sodium borohydride, reacting in a dimethyl sulfoxide solution, and finally washing, vacuum drying and crushing.
[0011] Preferably, the mesh size of the polyetheretherketone powder is 800-1000 mesh and the density is 1.3 g / cm 3 , the melt index is 5g / 10min~120g / 10min.
[0012] Preferably, the mass ratio of the polyetheretherketone powder to sodium borohydride is 1-5:1.
[0013] Preferably, the reaction temperature is 100° C. to 140° C., and the reaction time is 12 h to 24 h.
[0014] Preferably, the vacuum drying temperature is 80° C., and the vacuum drying time is 24 h.
[0015] Preferably, the auxiliary filler comprises an esterification reaction catalyst and an external lubricant, and the mass ratio of the esterification reaction catalyst to the external lubricant is 1 to 5:1;
[0016] The silane coupling agent is KH550.
[0017] Preferably, the esterification reaction catalyst is a mixture of 4-dimethylaminopyridine and dicyclohexylcarbodiimide, and the mass ratio of 4-dimethylaminopyridine to dicyclohexylcarbodiimide is 1-2:1;
[0018] The external lubricant is calcium stearate.
[0019] The present invention also provides a method for preparing the polyetheretherketone-based composite material, comprising the following steps:
[0020] S1. placing the dried graphite in an aqueous solution of a silane coupling agent and ultrasonically dispersing it, washing it with anhydrous ethanol and then drying it to obtain modified graphite containing active groups (-OH, -COOH, etc.) on the surface;
[0021] S2, putting hydroxylated polyetheretherketone powder, carboxyl-containing polytetrafluoroethylene, modified graphite, silane coupling agent, esterification reaction catalyst and external lubricant into a high-speed mixer to mix to obtain a premix;
[0022] S3, putting the premix obtained in step S2 into a twin-screw extruder, extruding, cooling, and pelletizing to obtain a polyetheretherketone composite material.
[0023] Preferably, the concentration of the aqueous solution of the silane coupling agent is 20%.
[0024] Preferably, the extrusion temperature is 340°C to 380°C.
[0025] Compared with the prior art, the specific beneficial effects of the present invention are:
[0026] First, the present invention utilizes a silane coupling agent to perform surface modification on graphite using an impregnation method to obtain modified graphite containing active groups on the surface, thereby improving the problem of poor dispersion of graphite in a PEEK resin matrix; secondly, the present invention utilizes sodium borohydride with strong reducing properties to prepare hydroxyl-containing polyetheretherketone powder, and then adds polytetrafluoroethylene with a carboxyl group, and utilizes the wear resistance and self-lubricating properties of polytetrafluoroethylene and graphite, as well as the esterification reaction between hydroxylated PEEK and carboxylated polytetrafluoroethylene, to prepare a PEEK composite material with high wear resistance and high mechanical strength using a blending-melting method. It has been verified that the average friction coefficient and volume wear rate of the composite material provided by the present invention are compared with those of pure PEEK, respectively, and have increased from the original 0.44 and 0.0020 mm 3 s -1 Optimized to 0.16, 0.0007mm 3 s -1 , which greatly improves the wear resistance and self-lubricating properties of the original polyetheretherketone resin. DETAILED DESCRIPTION
[0027] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as limiting the present invention.
[0028] In particular, the preparation method of the carboxyl-containing polytetrafluoroethylene described in the following examples is prepared by referring to the method in Chinese patent document CN109966930A "A method for preparing a solid-phase grafted high-efficiency polytetrafluoroethylene surface monocarboxylation water treatment membrane".
[0029] Example 1.
[0030] 75 parts of polyetheretherketone powder, 25 parts of carboxyl-containing polytetrafluoroethylene, and 15 parts of graphite were placed in a vacuum drying oven and vacuum dried at 150° C. for 6 hours.
[0031] The dried polyetheretherketone powder and the strong reducing agent sodium borohydride were uniformly mixed in a mass ratio of 2.5:1, poured into a dimethyl sulfoxide solution, reacted at 120°C for 18 hours, cooled to room temperature, and then the solid precipitate was washed with ethanol, hydrochloric acid solution and deionized water in turn, vacuum dried at 80°C for 24 hours, and crushed to obtain hydroxylated polyetheretherketone powder.
[0032] The dried graphite was placed in an aqueous solution of silane coupling agent KH550 with a concentration of 20% and ultrasonically dispersed for 20 minutes, then washed and dried with anhydrous ethanol to obtain modified graphite HGr.
[0033] 70 parts of hydroxylated polyetheretherketone powder, 20 parts of carboxyl-containing polytetrafluoroethylene, 10 parts of modified graphite HGr, 3 parts of silane coupling agent KH550, 3 parts of esterification reaction catalyst (wherein the mass ratio of 4-dimethylaminopyridine to dicyclohexylcarbodiimide is 2:1), and 3 parts of calcium stearate are put into a high-speed mixer and mixed for 20 minutes to obtain a premix.
[0034] The obtained premix was put into a twin-screw extruder, extruded at 380°C, cooled, and pelletized to obtain a wear-resistant PEEK composite material, which was recorded as HGr-PEEK-1.
[0035] Example 2.
[0036] 85 parts of polyetheretherketone powder, 15 parts of carboxyl-containing polytetrafluoroethylene, and 15 parts of graphite were placed in a vacuum drying oven and vacuum dried at 150° C. for 6 hours.
[0037] The dried polyetheretherketone powder and the strong reducing agent sodium borohydride were uniformly mixed in a mass ratio of 2.5:1, poured into a dimethyl sulfoxide solution, reacted at 120°C for 18 hours, cooled to room temperature, and the solid precipitate was washed with ethanol, hydrochloric acid solution and deionized water in turn, vacuum dried at 80°C for 24 hours, and crushed to obtain hydroxylated polyetheretherketone powder.
[0038] The dried graphite was placed in an aqueous solution of silane coupling agent KH550 with a concentration of 20% and ultrasonically dispersed for 20 minutes, then washed and dried with anhydrous ethanol to obtain modified graphite HGr.
[0039] 80 parts of hydroxylated polyetheretherketone powder, 10 parts of carboxyl-containing polytetrafluoroethylene, 10 parts of modified graphite HGr, 1 part of silane coupling agent KH550, 1 part of esterification reaction catalyst (wherein the mass ratio of 4-dimethylaminopyridine to dicyclohexylcarbodiimide is 2:1), and 3 parts of calcium stearate are put into a high-speed mixer and mixed for 20 minutes to obtain a premix.
[0040] The obtained premix was put into a twin-screw extruder, extruded at 380°C, cooled, and pelletized to obtain a wear-resistant PEEK composite material, which was recorded as HGr-PEEK-2.
[0041] Example 3.
[0042] 55 parts of polyetheretherketone powder, 35 parts of carboxyl-containing polytetrafluoroethylene, and 25 parts of graphite were placed in a vacuum drying oven and vacuum dried at 150° C. for 6 hours.
[0043] The dried polyetheretherketone powder and the strong reducing agent sodium borohydride were uniformly mixed in a mass ratio of 2.5:1, poured into a dimethyl sulfoxide solution, reacted at 120°C for 18 hours, cooled to room temperature, and the solid precipitate was washed with ethanol, hydrochloric acid solution and deionized water in turn, vacuum dried at 80°C for 24 hours, and crushed to obtain hydroxylated polyetheretherketone powder.
[0044] The dried graphite was placed in an aqueous solution of silane coupling agent KH550 with a concentration of 20% and ultrasonically dispersed for 20 minutes, then washed and dried with anhydrous ethanol to obtain modified graphite HGr.
[0045] 50 parts of hydroxylated polyetheretherketone powder, 30 parts of carboxyl-containing polytetrafluoroethylene, 20 parts of modified graphite HGr, 3 parts of silane coupling agent KH550, 3 parts of esterification reaction catalyst (wherein the mass ratio of 4-dimethylaminopyridine to dicyclohexylcarbodiimide is 2:1), and 3 parts of calcium stearate are put into a high-speed mixer and mixed for 20 minutes to obtain a premix.
[0046] The obtained premix was put into a twin-screw extruder, extruded at 380°C, cooled, and pelletized to obtain a wear-resistant PEEK composite material, which was recorded as HGr-PEEK-3.
[0047] Example 4.
[0048] 55 parts of polyetheretherketone powder, 45 parts of carboxyl-containing polytetrafluoroethylene, and 15 parts of graphite were placed in a vacuum drying oven and vacuum dried at 150° C. for 6 hours.
[0049] The dried polyetheretherketone powder and the strong reducing agent sodium borohydride were uniformly mixed in a mass ratio of 2.5:1, poured into a dimethyl sulfoxide solution, reacted at 120°C for 18 hours, cooled to room temperature, and the solid precipitate was washed with ethanol, hydrochloric acid solution and deionized water in turn, vacuum dried at 80°C for 24 hours, and crushed to obtain hydroxylated polyetheretherketone powder.
[0050] The dried graphite was placed in an aqueous solution of silane coupling agent KH550 with a concentration of 20% and ultrasonically dispersed for 20 minutes, then washed and dried with anhydrous ethanol to obtain modified graphite HGr.
[0051] 50 parts of hydroxylated polyetheretherketone powder, 40 parts of carboxyl-containing polytetrafluoroethylene, 10 parts of modified graphite HGr, 1 part of silane coupling agent KH550, 5 parts of esterification reaction catalyst (wherein the mass ratio of 4-dimethylaminopyridine to dicyclohexylcarbodiimide is 2:1), and 3 parts of calcium stearate are put into a high-speed mixer and mixed for 20 minutes to obtain a premix.
[0052] The obtained premix was put into a twin-screw extruder, extruded at 380°C, cooled, and pelletized to obtain a wear-resistant PEEK composite material, which was recorded as HGr-PEEK-4.
[0053] Comparative Example 1.
[0054] 100 parts of polyetheretherketone powder, 3 parts of silane coupling agent KH550, and 3 parts of calcium stearate were put into a high-speed mixer and mixed for 20 minutes to obtain a premix.
[0055] The premix was extruded at 380° C. using a twin-screw extruder, cooled, and pelletized to obtain pure PEEK resin pellets, which were recorded as C-PEEK.
[0056] Comparative Example 2.
[0057] 90 parts of polyetheretherketone powder, 10 parts of carboxylated polytetrafluoroethylene, 2 parts of silane coupling agent KH550, and 3 parts of calcium stearate were put into a high-speed mixer and mixed for 20 minutes to obtain a premix.
[0058] The premix was extruded at 380° C. using a twin-screw extruder, cooled, and pelletized to obtain a PEEK composite material, which was recorded as P-PEEK.
[0059] Comparative Example 3.
[0060] 80 parts of polyetheretherketone powder, 10 parts of carboxylated polytetrafluoroethylene, 10 parts of graphite, and 3 parts of calcium stearate were put into a high-speed mixer and mixed for 20 minutes to obtain a premix.
[0061] The premix was extruded at 380° C. using a twin-screw extruder, cooled, and pelletized to obtain a PEEK composite material, which was recorded as PC-PEEK.
[0062] Effect example.
[0063] The friction performance of the materials prepared in Examples 1-4 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1.
[0064] Table 1 Material friction performance test results
[0065]
[0066] From the data in Table 1, it can be seen that the friction performance of the composite material obtained by directly melt blending and extruding granulation of conventional polyetheretherketone powder, conventional graphite and polytetrafluoroethylene in Comparative Examples 1-3 is still not ideal; on the basis of Comparative Example 3, the composite material obtained by modifying the polyetheretherketone powder and graphite by the preparation method of Examples 1-4 has significantly improved friction performance. A transfer film is formed between polytetrafluoroethylene and graphite, resulting in the average friction coefficient and volume wear rate of the composite material being increased from 0.44 and 0.0020 mm, respectively, compared with pure PEEK. 3 s -1 Optimized to 0.16, 0.0007mm 3 s -1, which greatly improves the wear resistance and self-lubricating properties of the original polyetheretherketone resin.
[0067] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A polyetheretherketone-based composite material, characterized in that: Contains the following components by mass: 50 to 90 parts of hydroxylated polyetheretherketone powder, 10 to 40 parts of carboxyl-containing polytetrafluoroethylene, 10 to 40 parts of modified graphite, 1 to 10 parts of silane coupling agent, and 3 to 10 parts of auxiliary filler; The hydroxylated polyetheretherketone powder is obtained by uniformly mixing dry polyetheretherketone powder and sodium borohydride, reacting in a dimethyl sulfoxide solution, and finally washing, vacuum drying and crushing; The modified graphite is obtained by surface-modifying graphite with a silane coupling agent using an impregnation method; The auxiliary filler includes an esterification catalyst and an external lubricant; The preparation method of the polyetheretherketone-based composite material comprises the following steps: The above components are put into a high-speed mixer for mixing to obtain a premix; the obtained premix is put into a twin-screw extruder for extrusion, cooling, and pelletizing to obtain a polyetheretherketone composite material.
2. The polyetheretherketone-based composite material according to claim 1, characterized in that: The mesh size of the polyetheretherketone powder is 800-1000 mesh and the density is 1.3 g / cm 3 , the melt index is 5g / 10min~120g / 10min.
3. The polyetheretherketone-based composite material according to claim 1, characterized in that: The mass ratio of the polyetheretherketone powder to sodium borohydride is 1-5:
1.
4. The polyetheretherketone-based composite material according to claim 1, characterized in that: The reaction temperature is 100° C. to 140° C., and the reaction time is 12 h to 24 h.
5. The polyetheretherketone-based composite material according to claim 1, characterized in that: The vacuum drying temperature is 80° C., and the vacuum drying time is 24 h.
6. The polyetheretherketone-based composite material according to claim 1, characterized in that: The mass ratio of the esterification reaction catalyst to the external lubricant is 1-5:1; and the silane coupling agent is KH550.
7. The polyetheretherketone-based composite material according to claim 6, characterized in that: The esterification reaction catalyst is a mixture of 4-dimethylaminopyridine and dicyclohexylcarbodiimide, and the mass ratio of the 4-dimethylaminopyridine to the dicyclohexylcarbodiimide is 1-2:1; and the external lubricant is calcium stearate.
8. A method for preparing a polyetheretherketone-based composite material according to any one of claims 1 to 7, characterized in that: The steps include: S1, placing the dried graphite in an aqueous solution of a silane coupling agent for ultrasonic dispersion, washing with anhydrous ethanol and then drying to obtain modified graphite containing active groups on the surface; S2, putting hydroxylated polyetheretherketone powder, carboxyl-containing polytetrafluoroethylene, modified graphite, silane coupling agent, esterification reaction catalyst and external lubricant into a high-speed mixer to mix to obtain a premix; S3, putting the premix obtained in step S2 into a twin-screw extruder, extruding, cooling, and pelletizing to obtain a polyetheretherketone composite material.
9. The method for preparing the polyetheretherketone-based composite material according to claim 8, characterized in that: The concentration of the aqueous solution of the silane coupling agent is 20%.
10. The method for preparing the polyetheretherketone-based composite material according to claim 8, characterized in that: The extrusion temperature is 340°C to 380°C.
Citation Information
Patent Citations
Preparation method of solid phase grafted high efficient polytetrafluoroethylene (PTFE) surface mono-carboxylated water treatment film
CN109966930A
Preparation method of lubricating resin composition
CN116082837A
Sizing agent based on high-dispersity composite filler, carbon fiber reinforced polyether-ether-ketone composite material modified by sizing agent and preparation method of carbon fiber reinforced polyether-ether-ketone composite material
CN116623425A